Sex differences in IV thrombolysis treatment for stroke: a systematic review and meta-analysis - Strong, Brent; Lisabeth, Lynda; Reeves, Mathew (Dryad, 2020)
Objective: A prior meta-analysis of reports published between 2000 and
2008 found that women were 30% less likely to receive IV rt-PA treatment
for stroke than men; we updated this meta-analysis to determine if this
sex difference still persisted. Methods: We identified studies that
reported sex-specific IV rt-PA treatment rates for acute ischemic stroke
published between 2008 and 2018. Eligible studies included representative
populations of ischemic stroke patients from hospital-based,
registry-based, or administrative data. Random effects odds ratios (OR)
were generated to quantify sex differences. Results: Twenty-four eligible
studies were identified during this 10-year period. The summary unadjusted
OR based on 17 studies with data on all ischemic stroke patients was 0.87
(95% confidence interval [CI]=0.82-0.93), indicating that women had 13%
lower odds of receiving IV rt-PA treatment than men. However, substantial
between-study variability existed. Lower treatment odds in women were also
observed in 7 studies that provided data on the subgroup of patients
eligible for IV rt-PA treatment, although the summary OR of 0.95 (95% CI =
0.88-1.02) was not statistically significant. Examination of time trends
across 33 studies published between 2000 and 2018 found evidence that the
sex difference had narrowed in more recent years. Conclusions: Although
there is considerable variability in the findings of individual studies,
pooled data from recent studies shows that women with acute stroke are
still less likely to be treated with IV thrombolysis compared with men.
However, the size of this difference has narrowed compared to studies
published before 2008.
Supplemental Figures and Tables, Study Exclusions and
References